2006
DOI: 10.1080/09537100500163358
|View full text |Cite
|
Sign up to set email alerts
|

A new definition of aspirin non-responsiveness by Platelet Function Analyzer-100™ and its predictors

Abstract: Definition of aspirin non-responsiveness as post-aspirin CTs < or =193 s might overestimate the prevalence of aspirin non-responsiveness. Nevertheless, definition of aspirin non-responsiveness by PFA-100 must be standardized and its utility as a predictor of cardiovascular events needs to be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…17 Multiplate Analyzer used in this study worked in whole blood through an impedance technique. A study by Corina et al 11 compared the two devices and techniques concludes that the results achieved with the bedside Multiplate assays were not different from those obtained with classical aggregometry for detecting the effects of aspirin and clopidogrel.…”
Section: Discussionmentioning
confidence: 99%
“…17 Multiplate Analyzer used in this study worked in whole blood through an impedance technique. A study by Corina et al 11 compared the two devices and techniques concludes that the results achieved with the bedside Multiplate assays were not different from those obtained with classical aggregometry for detecting the effects of aspirin and clopidogrel.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who had an Epi-CT <193 seconds were classified as AR. 20 Commercial enzyme-linked immunoassay test kits were used to measure plasma concentrations of high sensitive C-reactive protein (hs-CRP), soluble P-selectin, soluble CD40-ligand (sCD40L), soluble intercellular adhesion molecule-1 (ICAM-1), von Willebrand factor (vWF), and Dedimer. Test kits from R&D Systems, Inc. (Minneapolis, MN, USA) were used for measuring P-selectin, sCD40L, hs-CRP, and ICAM-1, and test kits from American Diagnostica, Inc. (Stamford, CT, USA) were used for measuring vWF and Dedimer.…”
Section: Participantsmentioning
confidence: 99%
“…However, the use of PFA-100 to define aspirin resistance does not rigorously identify a group that has aspirin resistance and the data obtained by using PFA-100 probably is more accurately described as platelet reactivity despite the use of aspirin [16]. Moreover, without knowing the pre-aspirin CT, some patients in the study population may be incorrectly classified as aspirin resistant detected by PFA-100 [26]. Abacı and colleagues [26] reported that the definition of aspirin resistance as having a normal CT might be inappropriate for the classification of some patients.…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, without knowing the pre-aspirin CT, some patients in the study population may be incorrectly classified as aspirin resistant detected by PFA-100 [26]. Abacı and colleagues [26] reported that the definition of aspirin resistance as having a normal CT might be inappropriate for the classification of some patients. In their theoretical example, if a patient's CT prolonged from 100 s to 190 s after aspirin treatment would be more responsive to aspirin than the patient whose CT prolonged from 170 s to 195 s after aspirin treatment.…”
Section: Discussionmentioning
confidence: 97%